(untitled) (Razão e Fé, 2026)
The focus of this article is to approach the horizon of Grace in the priestly dimension in the light of Patristic Theology. We take into account that the theme of Grace has developed as it has been understood in relation to God’s action in creation and history. However, with the advent of the Incarnation and the emergence of the Church, theological elaborations on divine grace were gaining more and more ground in theology. And among the many theological divergences on the question of grace, we will offer a vision of the Church fathers, in the fight against heresies that questioned the role of grace.